2000
DOI: 10.1093/ps/79.9.1311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc bacitracin and salinomycin on intestinal microflora and performance of broilers

Abstract: A feeding experiment was carried out over 42 d with four groups of broiler chickens fed experimental diets formulated to provide no supplementation, 20 mg zinc bacitracin, 60 mg salinomycin, or both feed additives in combination. During the fifth week of the experiment, four chickens from each pen were killed, and the contents of gizzard, duodenum, jejunum, ileum, ceca, and rectum were separately collected and pooled. In all intestinal segments, the pH and the concentration of lactic acid were measured, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
154
4
16

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(195 citation statements)
references
References 29 publications
21
154
4
16
Order By: Relevance
“…The increased in cholesterol concentration in the present study could be due to the phenolic compounds of carvacrol and thymol that exhibit considerable antimicrobial activity (Basilico and Basilico, 1999;Hernandez et al, 2004) that may depress fat absorption due to bile acid deconjugation (Engberg et al, 2000).…”
Section: Resultsmentioning
confidence: 72%
“…The increased in cholesterol concentration in the present study could be due to the phenolic compounds of carvacrol and thymol that exhibit considerable antimicrobial activity (Basilico and Basilico, 1999;Hernandez et al, 2004) that may depress fat absorption due to bile acid deconjugation (Engberg et al, 2000).…”
Section: Resultsmentioning
confidence: 72%
“…Since the PC group had significantly lower Lactobacillus counts, compared with the challenged control group (NC), it can be speculated that low microbial fermentation activities in the ileal digesta resulted in less volatile fatty acid production. Engberg et al (2000) also observed higher pH and lower lactate concentrations in ileal digesta of broilers fed diets supplemented with salinomycin alone or salinomycin and Zn-bacitracin. The present results also confirmed those of Engberg et al (2002) who found that lactate and acetate are the predominant organic acids produced due to bacterial fermentation in the ileum.…”
Section: Organic Acids and Phmentioning
confidence: 67%
“…Gunal et al (2006) reported that the addition of probiotics alone or a combination of probiotics with organic acid mixture treatments to diets decreased ileal and caecal gram-negative bacteria counts at 21 days or at 42 days. Engberg et al (2000) found that Enterococcus faecium (Cylactin) treatments to diets reduced aerobic and coliform bacteria counts. …”
Section: Resultsmentioning
confidence: 98%
“…and Clostridium perfringens has been reported, with pathogenic microflora being established in the small intestine, thereby competing with the host for nutrients and reducing the digestion of fat and fat-soluble vitamins owing to the deconjugating effects of bile acids (Engberg et al, 2000). This depresses growth performance and increases the incidence of disease.…”
Section: Introductionmentioning
confidence: 99%